Supervisi Bahasa Kelas (Classroom Language) Bagi Guru-Guru SMK JAKARTA PUSAT 1 - Vera Diana; R. Sri Ayu Indrapuri; Siti Suhariyah; Nurun Chasanah; Heni Novita Sari (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The presence of English has become part of the classroom language in schools. This is carried out as a form of contribution and enrichment of teacher professionalism in dealing with educational developments according to the demands of the times. However, there is still a lack of optimization of English competence in implementing classroom language mastery in the process of teaching and learning activities in schools. To maximize the basic competence of classroom language, SMK Jakarta Pusat 1 has implemented classroom language through gradual English language training. This is expected to improve the quality of human resources, schools, and be able to reflect on students to apply their English skills globally. Class language in general can be said as English expressions used in communicating in class between teachers and students. The teachers of SMK Central Jakarta 1 have been given language training in previous classes. After that, a supervision program for the use of classroom language was given between teachers and students. This supervision activity aims to improve the ability of teachers of SMK Central Jakarta 1 in mastering relevant and effective classroom language and stimulate students' competence to be able to speak English. The results of the questionnaire proved that all teachers responded positively and achieved good marks for non-English teachers. This means that the implementation of bilingualism in SMK Central Jakarta 1 can be effectively realized optimally.